POTENSI PENGEMBANGAN AGROFORESTRI MASYARAKAT SEKITAR HUTAN ADAT GHIMBO POMUAN, KAMPAR, RIAU - Anna, Anna Juliarti; Sukma RA, Dodi; Novia Yanti, Rina (Forestry Study Program University Of Mataram, 2024)
Agroforestry applied to community gardens/yards around the Ghimbo Pomuan Indigenous Forest has the potential to be developed. The purpose of the study was to analyze the potential for agroforestry development of the community around the Ghimbo Pomuan Indigenous Forest, Kampar Riau. The method used in this research is a survey method. The survey method was carried out by structured interviews through questionnaires, identifying and making an inventory of fruit trees and agriculture with agroforestry patterns. Interviews were conducted to determine the types of fruit trees and agricultural products that have the potential to be developed by the community around the Ghimbo Pomuan Indigenous Forest. The results showed that the respondent's perception of the agroforestry system based on the Likert scale value had an average of 4.01. This shows that the respondent's knowledge of the agroforestry system is good. There were 29 types of trees, fruit and, agricultural crops, consisting of 19 families and 27 genera which were planted in the garden/yard with the respondent's agroforestry pattern. Generally, tree species are dominated by fruit trees. The combination of species in the agroforestry pattern is dominated by woody plants, namely rubber (Hevea bransiliasis) and coconut (Cocos nucifera). Types of fruit plants are sweet orange, longan, and guava image (Syzygium aqueum). While agricultural crops are dominated by bananas, corn, and chilies. The choice of combination of types of plants with agroforestry patterns is dominated by banana with longan, matoa with rimbang, chili, jambu citra with cassava.